2010
DOI: 10.1007/s00213-010-2109-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the serotonin transporter (5-HTTLPR) and α2A-adrenoceptor (C-1291G) genotypes on substance use in children and adolescents: a longitudinal study

Abstract: Our results reveal that expression of genetic vulnerability for substance use in children and adolescents may depend on age, gender, interaction of genes, and type of substance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…However, there was also evidence for two direct effects. Those with the 5-HTTLPR SS genotype had higher rates of problematic alcohol use, which maps on to prior work with youth (Merenäkk et al, 2011). Mesolimbic serotonergic pathways have been demonstrated to play a critical role in the development of alcohol dependence and ethanol tolerance (Türker et al, 1998).…”
Section: Discussionmentioning
confidence: 60%
“…However, there was also evidence for two direct effects. Those with the 5-HTTLPR SS genotype had higher rates of problematic alcohol use, which maps on to prior work with youth (Merenäkk et al, 2011). Mesolimbic serotonergic pathways have been demonstrated to play a critical role in the development of alcohol dependence and ethanol tolerance (Türker et al, 1998).…”
Section: Discussionmentioning
confidence: 60%
“…This gene encodes alpha2A subtype and it contains no introns in either its coding or untranslated sequences. There is an extensive literature on the gene and many findings suggesting association to ADHD (e.g., Kim et al, 2010; Roman et al, 2005; Roman et al, 2003; Waldman et al, 2006), as well as metabolic traits (e.g., glycemic phenotypes, blood pressure) (for meta-analysis see Talmud et al, 2011) and substance abuse (Clarke et al, 2012; Merenakk et al, 2011; Prestes et al, 2007). Given the neurobiological implications, this gene should be considered a strong candidate in future alcohol abuse studies.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental manipulation of serotonergic levels in an animal study [12] showed that decreasing serotonergic functioning increased alcohol intake. Human observational studies, however, have yielded inconsistent results concerning the association of the 5-HTTLPR genotype with adolescent alcohol use [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 95%